Status Gizi Siswa Kelas IV dan V Sekolah Dasar Negeri 1 Sorobayan Gadingsari Kapanewon Sanden Kabupaten Bantul - Hidayat, Bachtiar Mukti (Jurnal Pendidikan Dasar dan Aktifitas Jasmani, 2025)
This research aims to determine the level of nutritional status of the fourth and fifth grade students of SD Negeri 1 Sorobayan (Sorobayan 1 Elementary School), Sanden District, Bantul Regency. Due to the lack of concentration of some students during learning and there are students’ unbalanced body postures between height and weight. The research method used a quantitative method. The data from this research were students at SD Negeri 1 Sorobayan, Sanden District, Bantul Regency with a total of 44 students consisted of 25 male students and 19 female students. The data collection technique involved measuring body weight and height using a weight scale (GEA) and a stadiometer (Stature Meter) to obtain data, then the data was calculated by using the BMI formula. Based on the research results, it shows that the nutritional status of the fourth and fifth grade students of SD N 1 Sorobayan, Sanden District, Bantul Regency has normal nutritional status, for about 11 students (39.11), then in the over nutritional category there are 4 students (47.29), and in the underweight category there are 26 students (31.14) and 3 students are in the obese category (49.27). Therefore, the frequency is in the poor category, thus the nutritional status of the fourth and fifth grade students of SD N 1 Sorobayan, Sanden District, Bantul Regency, is mostly poor.